ELECTRONIC VICTIMS - Tukhtasinov Alyorbek; Kuldoshev Otabek; Raxmatullayeva Maftuna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Maftunaraxmatullayeva1112@gmail.com Abstract. This article explores the phenomenon of phishing in the context of social engineering, a common form of cybercrime. Phishing involves deceptive methods used by "intelligence hackers" to encourage individuals to disclose confidential information or perform certain actions. The article explores the various manifestations of phishing attacks, their impact on victims, and the methods employed by cybercriminals. It highlights the importance of online security and provides practical advice on mitigating risks associated with phishing. The article concludes by emphasizing the need to raise awareness and vigilance to combat this growing threat.